Health effects of saturated and trans-fatty acid intake in children and adolescents: Systematic review and meta-analysis. - Lisa Te Morenga; Jason M Montez (PLoS ONE)
Background Elevated cholesterol has been linked to cardiovascular disease in adults and preclinical markers of atherosclerosis in children, thus reducing saturated (SFA) and trans-fatty acids (TFA) intake from an early age may help to reduce cholesterol and the risk of cardiovascular disease later in life. The aim of this review is to examine the evidence for health effects associated with reducing SFA and TFA intake in free-living children, adolescents and young adults between 2 to 19 years of age. Design Systematic review and meta-analysis of randomised controlled trials (RCTs) and prospective cohort studies. Study selection, assessment, validity, data extraction, and analysis were undertaken as specified by the Cochrane Collaboration and the GRADE working group. Data were pooled using inverse variance models with random effects. Data sources EMBASE; PubMed; Cochrane Central Register of Controlled Trials; LILACS; and WHO Clinical Trial Registry (up to July 2016). Eligibility criteria for selecting trials RCTs involving dietary interventions aiming to reduce SFA or TFA intakes and a control group, and cohort studies reporting the effects of SFA or TFA exposures, on outcomes including blood lipids; measures of growth; blood pressure; insulin resistance; and potential adverse effects. Minimum duration was 13 days for RCTs and one year for cohort studies. Trials of weight loss or confounded by additional medical or lifestyle interventions were excluded. Results Compared with control diets, there was a highly statistically significant effect of reduced SFA intake on total cholesterol (mean difference (MD) -0.16 mmol/l, [95% confidence interval (CI): -0.25 to -0.07]), LDL cholesterol (MD -0.13 mmol/l [95% CI:-0.22 to -0.03]) and diastolic blood pressure (MD -1.45 mmol/l [95% CI:-2.34 to -0.56]). There were no significant effects on any other risk factors and no evidence of adverse effects. Conclusions Advice to reduce saturated fatty acids intake of children results in a significant reduction in total and LDL-cholesterol levels as well as diastolic blood pressure without evidence of adverse effects on growth and development. Dietary guidelines for children and adolescents should continue to recommend diets low in saturated fat.